Zeaxanthin - Lee, Chi-Ching; Demirci, Mehmet; Lee, Chı-Chıng; Demirci, Mehmet (Springer, 2023)
Zeaxanthin is one carotenoid molecule commonly found in a variety of fruits and vegetables, such as yellow corn, saffron, orange juice, honeydew, goji berry, paprika, spinach, kale, romaine lettuce, zucchini, and brussels sprout. It is the pigment that provides red, yellow, and orange colors to many plants and even can be found in animal products like chicken egg yolk. It also belongs to the fat-soluble xanthophyll family which is the oxygenated derivatives of carotenes. The chemical structure of zeaxanthin is a symmetric polyene-like molecule containing nine alternating conjugated carbon double and single bonds. Zeaxanthin has two chiral centers but only three stereoisomeric forms because both stereoisomers, (3R, 3′S) – zeaxanthin and (3S, 3′R) – zeaxanthin, are identical. These two stereoisomers are also called meso-zeaxanthin found in the macula of the central retina and lutein found in peripheral regions of the retina since the macula is where the zeaxanthin and lutein are stored. Zeaxanthin offers several human health benefits with potential antioxidant ability and anti-inflammatory properties. Many studies showed that zeaxanthin and other carotenoids can decrease the risk of eye diseases such as age-related macular degeneration, cataracts, and glaucoma. Zeaxanthin not only protects human eyes from absorbing harmful blue light but also gets involved in the eye development of fetuses and optimal vision during young adulthood. This chapter will discuss the sources and properties of zeaxanthin, the methods of extraction and isolation of zeaxanthin, human health benefits of zeaxanthin, and the other applications.
BOOk TITLE: Handbook of Food Bioactive Ingredients -- Chapter name: Zeaxanthin: Sources, Properties and Benefits, LEE CHI-CHING, DEMİRCİ MEHMET, Yayın Yeri: Springer Nature, Editör:Jafari Seid Mahdi , Rashidinejad Ali, Simal-Gandara Jesus, Basım sayısı:1, Sayfa sayısı:628, ISBN:978-3-031-28109-9, Bölüm Sayfaları:653 -686
Keywords: Zeaxanthin; Lutein; Carotenoid; Eye health